BIOCHEMICAL AND MOLECULAR IDENTIFICATION OF ASPERGILLUS FLAVUS STRAIN MARUTY C1 FROM MARINE SEDIMENTS - D. SRI RAMI REDDY,; SATYA CH.V, (International Journal of Pharma and Bio Sciences, 2014)
L-asparaginase is a potential anti-carcinogenic enzyme. Microbial system plays the important role in the production of L-asparaginase enzyme. Collected marine samples were screened for potential producers of L-asparaginase using modified Czapek dox’s agar containing L-asparagine and phenol red indicator. The selected strain has been characterized by biochemical tests was found to be Aspergllus species. Based on the molecular characterization, 16SrDNA sequence was identified, strain have been closely related to Aspergillus flavus subsp CJ-B4 (100% similarity). As the organism was varied with substantial differences in some of the polyphasic and biochemical characteristics it was proposed as a strain variety of Aspergillus flavus and designated as Aspergillus flavus Maruty C1.